2023
DOI: 10.2147/idr.s434695
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Associated with Poor Prognosis of Acquired Immunodeficiency Syndrome Patients Complicated with Disseminated Talaromycosis marneffei

Lianpeng Wu,
Yong Pan,
Ke Xu

Abstract: To analyze the clinical characteristics of AIDS with dTSM, especially in patients with poor prognosis. Patients and Methods: One hundred and seventy AIDS patients were enrolled in this single-center retrospective study. The epidemiological characteristics, clinical manifestations, laboratory tests, imaging examination, and treatment outcome were collected. Logistic regression analysis was used to estimate the risk of mortality in AIDS patients with dTSM. The predictive value was evaluated using the receiver op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Over the past 20 years, TSM has progressed from a rare disease to a common co-infection in HIV patients, and studies have confirmed that TSM can increase the mortality rate of HIV patients, which is a severe threat to human life and health [ 8 ]. A number of studies have analyzed factors associated with poor prognosis of HIV-positive TSM patients [ 7 , [12] , [13] , [14] , [15] , [16] , [17] ]. However, there is a lack of research on the prognosis of severe HIV/AIDS patients with TSM.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, TSM has progressed from a rare disease to a common co-infection in HIV patients, and studies have confirmed that TSM can increase the mortality rate of HIV patients, which is a severe threat to human life and health [ 8 ]. A number of studies have analyzed factors associated with poor prognosis of HIV-positive TSM patients [ 7 , [12] , [13] , [14] , [15] , [16] , [17] ]. However, there is a lack of research on the prognosis of severe HIV/AIDS patients with TSM.…”
Section: Introductionmentioning
confidence: 99%